Synthesis and structure determination via ultra-fast electron diffraction of the new microporous zeolitic germanosilicate ITQ-62. Issue 17 (8th February 2018) - Bieseki, Lindiane; Simancas, Raquel; Jordá, Jose L.; Bereciartua, Pablo J.; Cantín, Ángel; Simancas, Jorge; Pergher, Sibele B.; Valencia, Susana; Rey, Fernando; Corma, Avelino
Abstract : A new multipore zeolite of 12–8 × 8 × 8 channel system, named ITQ-62, has been synthesized and its structure solved using electron diffraction tomography. Abstract : Here, we present the synthesis and structure determination of the new zeolite ITQ-62. Its structure was determined via ultra-fast electron diffraction tomography and refined using powder XRD data of the calcined material. This new zeolite contains a tridirectional channel system of highly distorted 8-rings, as well as a monodirectional 12-ring channel system.